The Woman Question: Interpellation Of Patriarchy (International Journal of Food and Nutritional Sciences, 2022)
This review paper examines the interpellation of patriarchy in Ruskin Bond's literary works, exploring how his stories and novels reflect the pervasive male dominance and its impact on women. Bond's narratives, set against the backdrop of Indian society, vividly portray the gender discrimination, exploitation, and societal expectations that confine women to subordinate roles. Through a detailed analysis of characters and themes in works such as "The Room on the Roof," "Delhi is not Far," and "Susanna's Seven Husbands," the paper highlights the constraints and sufferings of female characters. Despite the oppressive environment, Bond also acknowledges women's strength and resilience. The paper contextualizes Bond's representation of patriarchy within the broader sociological constructs and theories, offering insights into the overlapping social structures that perpetuate gender inequality. By critiquing the traditional roles and advocating for a feminist perspective, Bond's literature provides a critical lens on the patriarchal conventions of contemporary society. This review underscores the necessity of examining literary works to understand and challenge the entrenched norms of patriarchy, emphasizing Bond's contribution to the discourse on gender and societal dynamics.